1998
DOI: 10.1046/j.1365-2133.1998.02037.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous malignant melanoma in women and the role of oral contraceptives

Abstract: The role of oral contraceptives (OC) in the aetiology of cutaneous malignant melanoma (CMM) has been controversially discussed over the last two decades. In an extensive literature search we identified 18 case-control studies, published between 1977 and 1996, offering information on this relationship. Using a meta-analytical approach we combined the study-specific risk estimates and derived a summary odds ratio of 0.95 (95% confidence interval: 0.87-1.04). Based on the data of 3796 cases and 9442 controls, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 16 publications
(15 reference statements)
3
20
1
Order By: Relevance
“…Although the influence of endogenous estrogen on the outcome of melanoma in women had been suggested by earlier studies [20] more recent large clinical studies did not find this association to be significant [9,11,15]. Exogenous estrogens such as oral contraceptives and hormone-replacement therapy have been studied for many years for their potential to influence melanoma and although some studies supported an effect of exogenous estrogen on melanoma outcomes [21], other studies did not find this association to be significant [22][23][24][25]. Studies with smaller sample sizes found that women diagnosed with melanoma during pregnancy have increased risk of recurrence and mortality [26][27][28][29], but more recent large population based studies did not find any association between pregnancy and melanoma outcome [30][31][32].…”
Section: Female Sex Hormonesmentioning
confidence: 92%
“…Although the influence of endogenous estrogen on the outcome of melanoma in women had been suggested by earlier studies [20] more recent large clinical studies did not find this association to be significant [9,11,15]. Exogenous estrogens such as oral contraceptives and hormone-replacement therapy have been studied for many years for their potential to influence melanoma and although some studies supported an effect of exogenous estrogen on melanoma outcomes [21], other studies did not find this association to be significant [22][23][24][25]. Studies with smaller sample sizes found that women diagnosed with melanoma during pregnancy have increased risk of recurrence and mortality [26][27][28][29], but more recent large population based studies did not find any association between pregnancy and melanoma outcome [30][31][32].…”
Section: Female Sex Hormonesmentioning
confidence: 92%
“…In addition, there was no elevated risk seen in past users, even those with long past durations of use. 38 These data provide strong evidence against OCP use as a risk factor for the development of MM.…”
Section: Influence Of Hormones On Melanoma Key Pointsmentioning
confidence: 94%
“…However, these findings were based on a relatively small number of cases, and another cohort study found no excess risk (Adam et al, 1981). Subsequent case -control and cohort studies (Bain et al, 1982;Holly et al, 1983Holly et al, , 1995Holman et al, 1984;Helmrich et al, 1984;Beral et al, 1984;Gallagher et al, 1985;Green and Bain, 1985;Østerlind et al, 1988;Zanetti et al, 1990;Hannaford et al, 1991;Le et al, 1992;Palmer et al, 1992;Westerdahl et al, 1996;Gefeller et al, 1998;Smith et al, 1998;Feskanich et al, 1999) provided little evidence of an overall excess risk among ever users compared to never users, but a possible increase among long-term users (summarised in (Prentice and Thomas, 1987)). More recently, data from the Nurse's Health Studies indicated a risk of melanoma related to duration of oral contraceptive use, but only among current users (Feskanich et al, 1999).…”
mentioning
confidence: 99%